Pengaruh Citra Merk dan Harga terhadap Keputusan Pembelian Sepatu Adidas pada Kaum Muda di Kecamatan Kembangan Jakarta Barat - Nurhadi Fauzi; Usran Masahere (Jurnal Cakrawala Akademika, 2024)
This study examines the influence of price and brand image on the purchase decision of Adidas shoes among young people in Kembangan District, West Jakarta. Shoes have become a highly popular trend among Indonesian youth in recent years, as footwear and as a symbol of style and status. The development of the fashion industry in Indonesia continues to generate new trends, especially in various popular branded shoe brands. A non-probability sampling method was used to select 30 respondents wearing Adidas shoes in crowded places such as coffee shops. Data collection was conducted over one month. The results show that Brand Image (X1) has a positive and significant effect on Purchase Decision (Y) with count 2.266 > table 2.052 and significance 0.000 < 0.05. The Price variable (X2) also has a positive and significant effect with tcount 2.764 > ttable 2.052 and significance 0.010 < 0.05. The F test shows Fcount 11.023 > Ftable 3.340 with significance 0.000 < 0.05, concluding that Brand Image and Price simultaneously significantly affect the Purchase Decisions of young people in Kembangan District, West Jakarta. This research highlights the importance of price and brand image factors in marketing strategies for branded shoes targeting the youth market.